MINERALOGICAL, PETROLOGICAL AND GEOCHEMICAL FEATURES OF THE UNIQUE LAPIS LACEDAEMONIUS (KROKEATIS LITHOS) FROM LACONIA, GREECE: APPROACH ON PETROGENETIC PROCESSES WITHIN THE TRIASSIC VOLCANIC CONTEXT - Koutsovitis, P.; Kanellopoulos, C.; Passa, S.; Foni, K.; Tsapara, E.; Oikonomou, G.; Xirokostas, N.; Vallianatou, Κ.; Mouxiou, Ε. (Bulletin of the Geological Society of Greece, 2016)
The Lapis Lacedaemonius (krokeatis lithos) is a well-known meta-volcanic rock of great historical importance. Petrographic observations, mineral chemistry data, as well as geochemical analysis of selected samples, reveal that these rocks are porphyritic metabasaltic rocks which have been significantly affected by saussuritization and also by restricted silicification processes. They represent subduction related calc-alkaline volcanic rocks which also appear in the adjacent Hellenic Triassic volcanic outcrops, and appear to be associated with the rift/drift phase within the Pindos oceanic realm. The unique features of the Lapis Lacedaemonius, when compared to geochemically similar volcanic rock outcrops, are mainly attributed to their distinct porphyritic textures, predominantly with microlithically textured groundmass along with the coarse grained plagioclase, and to saussuritization processes. The Lapis Lacedaemonius seems to have been formed in a sub-volcanic system closely associated with epidosites, suggesting that metasomatism occurred within hydrothermal upflow zones.